Enhancement of thermoelectric performance of β-Zn4Sb3 through resonant distortion of electronic density of states doped with Gd1. Issue 22 (14th June 2015) - Ren, Baojin; Liu, Mian; Li, Xiaoguang; Qin, Xiaoying; Li, Di; Zou, Tianhua; Sun, Guolong; Li, Yuanyue; Xin, Hongxing; Zhang, Jian
<x xml:space="preserve">Abstract</x> The thermoelectric properties of Gd-doped β-Zn4Sb3 are investigated.